Forgotten connections: reviving the concept of upbringing in Scottish child welfare - Mark Smith (Scottish Journal of Residential Child Care)
The concept of upbringing is a central one in social pedagogy. It is also apparent in a Scottish social welfare tradition, most evidently in the 1964 Kilbrandon Report. Kilbrandon's broad understanding of upbringing or social education was, however, subsequently subsumed beneath increasingly compartmentalised and instrumental approaches to child care and education. These fail to adequately understand and, arguably, impede and distort adult responsibility for bringing up children. This article draws on European literature, and particularly the writing of the German social pedagogue Klaus Mollenhauer, to begin to articulate the concept of upbringing, locating it as the central task of child care and education. Bringing up children is identified as, fundamentally, a moral and cultural endeavour, brought about through caring, inter-generational relationships. The article concludes by suggesting that elements within a Scottish tradition and within current policy might be drawn on to support a broad understanding of upbringing.